Enhancing diffusion-weighted prostate MRI through self-supervised denoising and evaluation - Pfaff, Laura; Darwish, Omar; Wagner, Fabian; Thies, Mareike; Vysotskaya, Nastassia; Hoßbach, Julian; Weiland, Elisabeth; Benkert, Thomas; Eichner, Cornelius; Nickel, Dominik; Wuerfl, Tobias; Maier, Andreas (Scientific Reports, 2024)
Diffusion-weighted imaging (DWI) is a magnetic resonance imaging (MRI) technique that provides information about the Brownian motion of water molecules within biological tissues. DWI plays a crucial role in stroke imaging and oncology, but its diagnostic value can be compromised by the inherently low signal-to-noise ratio (SNR). Conventional supervised deep learning-based denoising techniques encounter challenges in this domain as they necessitate noise-free target images for training. This work presents a novel approach for denoising and evaluating DWI scans in a self-supervised manner, eliminating the need for ground-truth data. By leveraging an adapted version of Stein’s unbiased risk estimator (SURE) and exploiting a phase-corrected combination of repeated acquisitions, we outperform both state-of-the-art self-supervised denoising methods and conventional non-learning-based approaches. Additionally, we demonstrate the applicability of our proposed approach in accelerating DWI scans by acquiring fewer image repetitions. To evaluate denoising performance, we introduce a self-supervised methodology that relies on analyzing the characteristics of the residual signal removed by the denoising approaches.
CRIS-Team Scopus Importer:2024-10-25